EXCLI Journal; 22:Doc146; ISSN 1611-2156 2023
DOI: 10.17179/excli2022-5653
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib advanced mechanisms of action in multiple myeloma, solid and liquid tumors along with its novel therapeutic applications

Abstract: Bortezomib (BTZ) is a first-in-class reversible and selective proteasome inhibitor. It inhibits the ubiquitin proteasome pathway that leads to the degradation of many intracellular proteins. Initially, BTZ was FDA approved for the treatment of refractory or relapsed multiple myeloma (MM) in 2003. Later, its usage was approved for patients with previously untreated MM. In 2006, BTZ was approved for the treatment of relapsed or refractory Mantle Cell Lymphoma (MCL) and, in 2014, for previously untreated MCL. BTZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 178 publications
0
4
0
Order By: Relevance
“…Furthermore, considering the broad-spectrum activity of the compounds evaluated, they are likely to show significant efficacy against other pathogenic microorganisms. For instance, bortezomib corresponds to a pioneering proteasome inhibitor approved in 2003 by the FDA for the treatment of refractory or relapsed multiple myeloma [ 17 ]. It selectively and reversibly disrupts the ubiquitin-proteasome pathway, whose inhibition in the Leishmania genus is known to block parasite proliferation and differentiation, thereby altering its virulence factor [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, considering the broad-spectrum activity of the compounds evaluated, they are likely to show significant efficacy against other pathogenic microorganisms. For instance, bortezomib corresponds to a pioneering proteasome inhibitor approved in 2003 by the FDA for the treatment of refractory or relapsed multiple myeloma [ 17 ]. It selectively and reversibly disrupts the ubiquitin-proteasome pathway, whose inhibition in the Leishmania genus is known to block parasite proliferation and differentiation, thereby altering its virulence factor [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bortezomib is a first-in-class selective and reversible proteasome inhibitor, which binds to and inhibits the activity of the 26 S proteasome, a cellular complex responsible for degrading and recycling proteins. 546 , 547 By blocking the proteasome’s function, bortezomib was initially thought to inhibit IκB degradation, which is necessary for NF-κB activation. However, it has been later confirmed that bortezomib can also induce activation of canonical NF-κB signaling in multiple myeloma in vitro.…”
Section: Strategies For Targeting Nf-κb Signaling In Human Diseasesmentioning
confidence: 99%
“…Bortezomib, also known as Velcade, is the first selective proteasome inhibitor that demonstrated significant preclinical activity in several tumor models [28]. Moreover, it has been successfully used in patients with refractory or relapsed multiple myeloma, either as a single agent or combined with other therapies [29]. Recent studies demonstrated the potential use of Btz against AML [30][31][32].…”
Section: Introductionmentioning
confidence: 99%